Associations of urinary perchlorate, nitrate and thiocyanate with central sensitivity to thyroid hormones: A US population-based cross-sectional study. (June 2022) - King, Lei; Huang, Yue; Li, Tao; Wang, Qiang; Li, Wanyi; Shan, Zhilei; Yin, Jiawei; Chen, Liangkai; Wang, Pei; Dun, Changchang; Zhuang, Litao; Peng, Xiaolin; et al.
Graphical abstract: Highlights: Urinary perchlorate and thiocyanate were positively associated with central thyroid hormones sensitivity. Co-occurrence of perchlorate, nitrate, and thiocyanate was positively associated with central thyroid hormones sensitivity. The positive association of co-exposure of three anions with central thyroid hormones sensitivity was mostly attributed to thiocyanate. Abstract: Background: Perchlorate, nitrate, and thiocyanate are three well-known sodium iodine symporter inhibitors, however, associations of their individual and concurrent exposure with central thyroid hormones sensitivity remain unclear. Objectives: To investigate the associations of urinary perchlorate, nitrate, thiocyanate, and their co-occurrence with central thyroid hormones sensitivity among US general adults. Methods: A total of 7598 non-pregnant adults (weighted mean age 45.9 years and 52.9% men) from National Health and Nutritional Examination Survey 2007–2012 were included in this cross-sectional study. Central sensitivity to thyroid hormones was estimated with the Parametric Thyroid Feedback Quantile-based Index (PTFQI). Ordinary least-squares regression, weighted quantile sum (WQS) regression, and Bayesian kernel machine regression (BKMR) models were performed to examine the associations of three anions and their co-occurrence with PTFQI. Results: The weighted mean values of urinary perchlorate, nitrate, thiocyanate, and perchlorate equivalent concentration (PEC) were 5.48 μg/L, 57.59 mg/L, 2.65 mg/L, and 539.8 μg/L, respectively. Compared with the lowest quartile, the least-square means difference (LSMD) of PTFQI was −0.0516 (LSMD ± SE: −0.0516 ± 0.0185, P  < 0.01) in the highest perchlorate quartile. On average, PTFQI decreased by 0.0793 (LSMD ± SE: −0.0793 ± 0.0205, P  < 0.001) between the highest and lowest thiocyanate quartile. Compared with those in the lowest quartile, participants in the highest PEC quartile had significantly decreased PTFQI levels (LSMD ± SE: −0.0862 ± 0.0188, P  < 0.001). The WQS of three goitrogens, was inversely associated with PTFQI ( β : −0.051, 95% CI: −0.068, −0.034). In BKMR model, PTFQI significantly decreased when the levels of three anions were at or above their 60th percentiles compared to the median values. Conclusions: Higher levels of urinary perchlorate, thiocyanate, and co-occurrence of three goitrogens were associated with increased central thyroid hormones sensitivity among US general adults. Further studies are warranted to replicate our results and elucidate the underlying causative mechanistic links.